Phase Ib/II study of the pan-cyclin-dependent kinase inhibitor roniciclib in combination with chemotherapy in patients with extensive-disease small-cell lung cancer. (September 2018) - Cho, Byoung Chul; Dy, Grace K.; Govindan, Ramaswamy; Kim, Dong-Wan; Pennell, Nathan A.; Zalcman, Gerard; Besse, Benjamin; Kim, Joo-Hang; Koca, Goekben; Rajagopalan, Prabhu; Langer, Simon; Ocker, Matthias; et al.
Highlights: Phase Ib/II study of ED-SCLC patients treated with roniciclib plus chemotherapy. Combination was well tolerated and readily absorbed across all dose combinations. No clinically relevant PK interactions were observed upon concomitant treatment. Promising efficacy of roniciclib plus chemotherapy, despite low patient numbers. Unfavorable benefit/risk balance from another study led to study termination. Abstract: Objectives: This phase Ib/II study evaluated safety, pharmacokinetics, maximum tolerated dose (MTD), and efficacy of the pan-cyclin-dependent kinase inhibitor roniciclib with cisplatin-etoposide (CIS-ETOP) or carboplatin-etoposide (CARBO-ETOP) in patients with extensive-disease small-cell lung cancer (ED-SCLC). Patients and methods: In this open-label, non-randomized study, patients with previously untreated ED-SCLC received roniciclib twice daily (BID) in a 3 days on/4 days off schedule. Cisplatin 75 mg/m 2 or carboplatin (AUC5) dose was administered on day 1, and etoposide 100 mg/m 2 on days 1–3, of 21-day cycles. Phase Ib used a dose-escalation design to define the MTD for phase II. Pharmacokinetics were assessed. Results: Forty-three patients received treatment (roniciclib 2.5 mg BID [+ CARBO-ETOP, n = 4; + CIS-ETOP, n = 3] and roniciclib 5 mg BID [+ CARBO-ETOP, n = 24; + CIS-ETOP, n = 12]). The MTD of roniciclib was 5 mg BID with CARBO-ETOP or CIS-ETOP. Common adverse events were nausea (90.7%) and vomiting (69.8%). Roniciclib was readily absorbed following oral administration at the MTD (median tmax 0.5–1 h), with a 30–40% reduction in exposure when co-administered with CARBO-ETOP or CIS-ETOP; administration of roniciclib had no effect on etoposide or platinum pharmacokinetics. The response rate was 81.4% (35/43) overall and 86.1% (31/36) in the pooled roniciclib 5 mg BID population (all partial responses). Conclusion: Roniciclib co-administered with chemotherapy in patients with ED-SCLC demonstrated tolerability, acceptable pharmacokinetics, and promising efficacy. An observed safety signal in a related phase II study resulted in discontinuation of the present study and termination of further roniciclib development.